POTENSI SATASABANG SEBAGAI KAWASAN MINAPOLITAN DALAM ROADMAP SISTEM INOVASI DAERAH KABUPATEN LABUHANBATU DENGAN ANALISIS SWOT - Siti Masliyah Lubis (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
The purpose of the research is to identify and analyze the potential that can be developed in Satasabang as a minapolitan area which is on the agenda in the Labuhanbatu Regency RIS Roadmap for 2021-2026. This study describes the results of the data obtained qualitatively. Secondary data sources come from the regional apparatus and the Central Statistics Agency of Labuhanbatu Regency. Primary data in the form of interviews and observations with questionnaire instruments. The research location is in the villages of Sei Sakat, Sei Tawar, Sei Sanggul and Sei Berombang, Panai Hilir District, Labuhanbatu Regency. Data collection by survey method, observation and open interview to respondents. The research time is from January to May 2021. Data analysis uses SWOT. The identification results show the potential for abundant catches, but requires institutional support, infrastructure, capacity building and fishermen's capabilities. The results of the analysis using the SWOT measurement obtained a score of 61 points for the total strengths and opportunities, while the total weaknesses and challenges reached 71 points. Development efforts through the SIDa Roadmap of the Satasabang Area into a Minapolitan Area.